Dynamic residential load scheduling based on adaptive consumption level pricing scheme - Haider H.T.; See O.H.; Elmenreich W. (Elsevier Ltd, 2023)
Costs; Domestic appliances; Electric power transmission networks; Electric utilities; Energy utilization; Housing; Sales; Scheduling; Demand response; Dynamic pricing; Information and Communication Technologies; Load scheduling; Smart grid; Smart power grids